Magnetic Resonance Imaging in the Differential Diagnosis of Multiple Sclerosis and Other Demyelinating Diseases - Krotenkova, I. A.; Bryukhov, V. V.; Konovalov, R. N.; Zakharova, M. N.; Krotenkova, M. V. (Vestnik rentgenologii i radiologii, 2019)
The diagnosis of multiple sclerosis (MS) is quite complicated, which is associated with its clinical features and the lack of unique confirmatory tests. Magnetic resonance imaging (MRI) is one of the ways to confirm the diagnosis and also makes it possible to establish a differential diagnosis with other demyelinating diseases and to exclude diseases that mimic MS. This review presents not only MRI criteria for MS and other diseases similar to the MRI pattern, but also additional clinical and laboratory data, without which it is impossible to make a correct diagnosis.